Differences in dry eye questionnaire symptoms in two different modalities of contact lens wear: silicone-hydrogel in daily wear basis and overnight orthokeratology - García-Porta, Nery (2016)
Purpose. To compare the ocular surface symptoms and signs in an adult population of silicone-hydrogel (Si-Hy) contact lens (CL) wearers with another modality of CL wear, overnight orthokeratology (OK). Materials and Methods. This was a prospective and comparative study in which 31 myopic subjects were fitted with the same Si-Hy CL and 23 underwent OK treatment for 3 months. Dry eye questionnaire (DEQ) was filled in at the beginning of the study and then after 15 days, 1 month, and 3 months using each CL modality. The tear quality was evaluated with noninvasive tear break-up time. Tear production was measured with Schirmer test. Tear samples were collected with Schirmer strips being frozen to analyze the dinucleotide diadenosine tetraphosphate (Ap4A) concentration with High-Performance Liquid Chromatography (HPLC). Results. After refitting with ortho-k, a reduction in discomfort and dryness symptoms at the end of the day ( < 0.05, 2 ) was observed. No significant changes were observed in Ap4A concentration in any group. Bulbar redness, limbal redness, and conjunctival staining increased significantly in the Si-Hy group ( < 0.05, Kruskal–Wallis test). Conclusion. Discomfort and dryness symptoms at the end of the day are lower in the OK CL group than in the Si-Hy CL group.